Influence of Proactive Behavior on Employee Performance: The Case of Ministry of Education, Science and Technology in Kenya - Ramneek, Chaudhary; Alok, Kumar (Journal of Global Economy, Business and Finance, 2025)
Employee’s proactive behavior is one of the attributes of workforce agility. The behavior presents the capability to think quickly and in an intelligent way and supports the skill of individuals to proactively overcome obstacles or create opportunities by rethinking usual approaches. This study investigated the influence of proactive behavior on employee performance in the Ministry of Education Science and Technology (MoEST) in Kenya. The study was founded on Self Determination Theory and adopted a positivism philosophy. Using a cross - sectional survey, from a target population of 2116 employees, a sample size of 416 employees was drawn from selected using purposive sampling technique. A pilot study was conducted from MoEST employees in the in Laikipia, Isiolo and Meru counties to pretest the data collection instrument. Descriptive analysis, test of regression assumptions, and bivariate linear was used for inferential analysis. The results indicated that proactive behavior was associated with R - Square of.830, F - statistic of 654.666 and p - value of.000, a beta coefficient value of β=0.739 and associated p - value of.000 <.05. These results imply the proactive behavior had a positive and statistically significant influence on employees’ performance. Based on these findings, the study recommends that the Ministry and Public service at large should initiate where necessary and enhance capacity building programs on employee proactive behavior as it can explain over 80% of the variations in an employee’s performance. Further the study recommends that employee proactive behavior should be a monitored over time to sustain performance. Further, this behavior should be considered a strong variable of interest during entry level and promotion evaluation criteria in addition to respective employee technical skills.